Uma investigação sobre desenvolvimento baseado em testes com aplicação de critérios de teste no ensino introdutório de programação - Feitosa, Yuri Rafael Grajefe (2023)
Context: This master’s thesis is a research on the use of software testing techniques applied in Computer education, more specifically, in introductory programming teaching, for this is purposed the use of TDD (Test-driven development) to help learning based on testing criteria. This method seeks to better structure the student’s logical reasoning in the first steps with programming, avoiding trial and error. Objective: The work consists of proposing a new method of approach to teaching introductory programming disciplines using test criteria. This new format consists of using test case in code development, the student must first develop the test cases and then develop the algorithm, in this sense, thinking better about solving the problem before developing the code. Method: For this research, programming exercises were applied to students in the classroom. The sample was divided into two groups, the first group used test-first, the second did not. The exercises were monitored and sent for analysis with the help of framework for unit testing in C. Results: There are indications of improvements in the quality of programs developed by students with the aid of test criteria. Conclusions: Considering the evidence from related work on teaching programming with software testing and the final result of the research, the use of test criteria contributes to a better development of computational problems.